2018
DOI: 10.1039/c7nh00167c
|View full text |Cite
|
Sign up to set email alerts
|

A programmable lipid-polymer hybrid nanoparticle system for localized, sustained antibiotic delivery to Gram-positive and Gram-negative bacterial biofilms

Abstract: Lipid-polymer hybrid nanoparticle enhances antibiotic efficacy through localised, sustained delivery to bacterial biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
0
30
1
Order By: Relevance
“…The positive surface charge also provides higher binding affinity toward both planktonic bacteria and biofilms, providing localized delivery and minimizing systemic exposure, whereas the polymeric core contributes to the sustained antibiotic release to bacterial biofilms shown in our previous study. 21 On the basis of our conjecture from previous studies, LPNs can be engulfed by the professional phagocytes through phagocytosis, which is the same transport pathway as pathogens. This allows the loaded antibiotic to be delivered into the infected cells, thereby enhancing its penetration against intracellular pathogens.…”
mentioning
confidence: 88%
“…The positive surface charge also provides higher binding affinity toward both planktonic bacteria and biofilms, providing localized delivery and minimizing systemic exposure, whereas the polymeric core contributes to the sustained antibiotic release to bacterial biofilms shown in our previous study. 21 On the basis of our conjecture from previous studies, LPNs can be engulfed by the professional phagocytes through phagocytosis, which is the same transport pathway as pathogens. This allows the loaded antibiotic to be delivered into the infected cells, thereby enhancing its penetration against intracellular pathogens.…”
mentioning
confidence: 88%
“…Liposome composed of soy lecithin and cholesterol (5 : 1) was found to extend the stable period of cinnamon oil for 96 h and enhance its anti-biofilm activities against MRSA by over ten times, as compared to free cinnamon oil (Cui et al 2016). In context of the horizontal transmission of antimicrobial resistance genes, liposomes can not only efficiently 'sneak' into the interior of a biofilm, but also 'mask' the encapsulated drug from the cells until it reaches its destination and burst, so that the cells do not immediately recognize the 'intruder' and develop resistance through gene transfer (Van Bambeke et al 2008;Meng et al 2016;Rukavina and Vanic 2016;Baek et al 2018;Ramos et al 2018). For instance, it was reported that wheat germ agglutinin-modified liposomes as a drug carrier enhanced the antimicrobial efficiency of clarithromycin against MRSA by overcoming several resistance-associated phenotypic changes such as thickened cell wall and overexpression of efflux pumps (Meng et al 2016).…”
Section: Advantages and Limitations Of Liposome As A Drug Carriermentioning
confidence: 99%
“…However, it was observed that the phosphatidylcholine (PC)-based monolayer on the hybrid nanoparticles did not prompt the biofilm affinity. In contrast, a cationic lipid (i.e., 1,2-dioleoyl-3-trimethylammonium-propane, DOTAP) shell enabled the LPNPs to anchor onto surfaces of a diverse range of Gram-positive and Gram-negative bacterial pathogens [148]. However, the positive charge may impair the mucus-penetrating property, thus be inefficient in the treatment of respiratory tract infections.…”
Section: Lipid-enveloped Polymeric Nanoparticlesmentioning
confidence: 99%